2018
DOI: 10.18311/jeoh/2018/19992
|View full text |Cite
|
Sign up to set email alerts
|

Length Weight Relationship (LWR) and Condition Factor (K) of Brown Trout, Salmo trutta fario

Abstract: Length-weight relationships and condition factor of Salmo trutta fario (Brown trout) at Kokernag trout fish farm, Anantnag, Jammu and Kashmir was estimated for a period of one year. During the present study the fish samples was within the range of 30cm to 45.8cm in length and 250g to 750g in weight were originally used to provide information on the condition of fish and to determine whether somatic growth was isometric or allometric. The relationship was analysed using the formula W = a L b which was further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…In the present study, changes in the HSI indicate how the different diets affect the liver health of the cobia. An increase in HSI might suggest liver enlargement, which could be due to increased energy storage, detoxification, or other metabolic processes as the results shows in the present study when the fish were fed with the formulated diet [30,31]. Conversely, a decrease in HSI indicates that the liver is under less stress and the fish are allocating energy more toward growth, hence the frozen fresh fish is better suited for the cobia HSI needs.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In the present study, changes in the HSI indicate how the different diets affect the liver health of the cobia. An increase in HSI might suggest liver enlargement, which could be due to increased energy storage, detoxification, or other metabolic processes as the results shows in the present study when the fish were fed with the formulated diet [30,31]. Conversely, a decrease in HSI indicates that the liver is under less stress and the fish are allocating energy more toward growth, hence the frozen fresh fish is better suited for the cobia HSI needs.…”
Section: Discussionsupporting
confidence: 48%
“…HSI is a measure of the liver's relative size compared to the whole body. Changes in HSI can reflect alterations in liver health, metabolic activity, or energy allocation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Cyprinid species have the highest CF just before spawning (Erk'akan et al 2013;etc. ), which is in spring, while salmonid species have the highest CF just in the period when the eel has the lowest value (Rawat et al 2014;Jan et al 2018). In this case, specimens with lower CF than others will probably not spawn, ie.…”
Section: Discussionmentioning
confidence: 99%
“…The GSI and fecundity are believed to be very important measures that define the reproductive capacity of fish 36,37 . GSI could reflect the changes in the nutritional and energy status of fish while variations in the GSI and fecundity are pointers to the reproductive season of the fish and the incidence of spawning 38 . In this work, GSI was highest significantly in fish receiving the control feed which was similar to fish receiving other turmeric-supplemented feeds except for F, B, E and C. The result indicated that the inclusion of turmeric did not impose any reproductive advantage over fish on the control diet.…”
Section: Discussionmentioning
confidence: 99%